Flare quasi-periodic pulsation associated with recurrent jets - Li, Dong; Shi, Fanpeng; Zhao, Haisheng; Xiong, Shaolin; Song, Liming; Peng, Wenxi; Li, Xinqiao; Chen, Wei; Ning, Zongjun (Frontiers in Astronomy and Space Sciences, 2022)
Quasi-periodic pulsations (QPPs), which carry time features and plasma characteristics of flare emissions, are frequently observed in light curves of solar/stellar flares. In this paper, we investigate non-stationary QPPs associated with periodic jets during an M1.2 flare on 2022 July 14. A quasi-period of ~45$±$10~s, determined by the wavelet transform technique, is simultaneously identified at wavelengths of soft/hard X-ray and microwave emissions, which are recorded by the Gravitational wave high-energy Electromagnetic Counterpart All-sky Monitor, Fermi, and the Nobeyama Radio Polarimeters, respectively. A group of recurrent jets with an intermittent cadence of about 45$±$10~s are found in Atmospheric Imaging Assembly (AIA) image series at 304 Å, but they are 180-s earlier than the flare QPP. All observational facts suggest that the flare QPP could be excited by recurrent jets, and they should be associated with nonthermal electrons that are periodically accelerated by a repeated energy release process, like repetitive magnetic reconnection. Moreover, the same quasi-period is discovered at double footpoints connected by a hot flare loop in AIA 94 Å, and the phase speed is measured to ~1420 km s$^{-1}$. Based on the differential emission measure, the average temperatures, number densities, and magnetic field strengths at the loop top and footpoint are estimated to ~7.7/6.7 MK, ~7.5/3.6$×$10$^{10}$ cm$^{-3}$, and ~143/99~G, respectively. Our measurements indicate that the 45-s QPP is probably modulated by the kink-mode wave of the flare loop.